2020
DOI: 10.3390/ani10010127
|View full text |Cite
|
Sign up to set email alerts
|

Musical Dogs: A Review of the Influence of Auditory Enrichment on Canine Health and Behavior

Abstract: Music therapy yields many positive health outcomes in humans, but the effects of music on the health and welfare of nonhuman animals vary greatly with the type of music played, the ethology of the species, and the personality and learning history of individual animals. One context in which music therapy may be used to enhance animal welfare is to alleviate stress in domestic environments. Here, we review studies of the effects of music exposure on dogs as a case study for the implementation of music therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…One study indicated that music specifically designed for cats, but not classical music, was associated with fewer stress indicators and reduced resistance to handling in cats during a clinical examination compared to no background music [ 58 ]. In dogs, some studies suggest a possible calming effect of music (reviewed in [ 59 ]), but a study performed in a veterinary context could not demonstrate a reduction in fearful or aggressive behaviour [ 46 ]. However, the owners found the waiting time more pleasant, and the veterinarians indicated that they enjoyed the music [ 46 ].…”
Section: Creating a Low-stress Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated that music specifically designed for cats, but not classical music, was associated with fewer stress indicators and reduced resistance to handling in cats during a clinical examination compared to no background music [ 58 ]. In dogs, some studies suggest a possible calming effect of music (reviewed in [ 59 ]), but a study performed in a veterinary context could not demonstrate a reduction in fearful or aggressive behaviour [ 46 ]. However, the owners found the waiting time more pleasant, and the veterinarians indicated that they enjoyed the music [ 46 ].…”
Section: Creating a Low-stress Environmentmentioning
confidence: 99%
“…However, the owners found the waiting time more pleasant, and the veterinarians indicated that they enjoyed the music [ 46 ]. Further studies are needed to address species-specific preferences, as well as individual responses [ 59 ].…”
Section: Creating a Low-stress Environmentmentioning
confidence: 99%
“…Underwater noises are still important, and the effects of these anthropogenic sounds are now well described in the scientific literature. Taking account of this world concern, this project could be seen as an alternative to contribute to cetacean welfare, as music is used as a tool to decrease stress for some animal species (Alworth and Buerkle, 2013;Dhungana et al, 2018), for example, like gorillas (Wells et al, 2006), horses (Eyraud et al, 2019), and domestic species (Hampton et al, 2020;Lindig et al, 2020). Of course, this beneficial effect on stress will have to be proven on humpback whales, for example, by requiring cortisol monitoring (Rolland et al, 2012;Mingramm et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that music specifically designed for cats (but not classical music) was associated with fewer stress indicators and reduced resistance to handling during a clinical examination compared to no background music [50]. In dogs, some studies suggest a possible calming effect of music (reviewed in [51], but the only study performed in a veterinary context could not demonstrate a reduction in fearful or aggressive behaviour. However, owners found the waiting time more pleasant and veterinarians indicated that they enjoyed the music [50].…”
Section: Sensory Considerationsmentioning
confidence: 99%
“…However, owners found the waiting time more pleasant and veterinarians indicated that they enjoyed the music [50]. Further studies are needed to adress species-specific preferences, as well as individual responses [51].…”
Section: Sensory Considerationsmentioning
confidence: 99%